BEBERAPA SIFAT DAN PEMANFAATAN ARANG DARI SERASAH DAN KULIT KAYU PINUS - Sri Komarayati; Dadang Setiawan; Mahpudin Mahpudin (Pusat Penelitian dan Pengembangan Hasil Hutan, 2004)
This paper deals with a study on the properties, quality and uses of charcoal made from pine litter and bark. The study was intended to see the possibility of using pine litter and bark for compost, mixture of compost charcoal manufacturing, and growing media. The abundance of pine litter and bark left on the forest floor initiated this study. Only some of the pine bark was used for fuel.The results revealed that the charcoal made from pine litter and bark showed the following properties: moisture content at 5.23 - 7.81 percent ; ash content 1.88 - 13. 76 percent ; volatile matter 26.19- 32.60 percent; fixed carbon 53.63 - 71.93 percent, and colorivic value 7192 cal/gr. The macro-nutrient content of pine bark was categorized as moderate for N-total, P205, K20 and water-based pH, as high for C organic and C/N ratio, and as low for CaO and MgO. The quality of compost and compost charcoal made from pine litter and bark met the related standard, among others. Pat 1.12- 1.24 percent; K 1.47- 1,62 percent ; Mg 0.67- 1.05 percent; moisture content 55.81 - 56.21 percent; pH 6.8- 7.2 and C/N ratio 18.89- 20.10.